KINERJA UNIT PELAYANAN TERPADU PENANGGULANGAN KEMISKINAN (UPTPK) DALAM PERBAIKAN RUMAH TIDAK LAYAK HUNI DI KABUPATEN SRAGEN - Dahana, Gilang Akbar (JI@P, 2019)
The purpose of this study is to describe a performance Integrated povertyreduction Service Unit (UPTPK) in the repair of the House is not Livablein Sragen.Type of this research is a descriptive qualitative research. Theresesrch colleced of data using interviews and documentation. Thevalidity of the data using a data triangulation in which researchers usemultiple data sources to collect the same data. Data analysis techniquesusing interactive analysis. Based on the results of the research on theperformance of the policy of home repairs are not feasible based on theregulations of Regent Sragen number 11 Year 2017 About Guidelines thegranting of social assistance Expenditures shows that organizationalperformance UPTPK Sragen is already optimal. It appears from theproductivity performance of UPTPK Sragen district in homeimprovement is not Livable (RTLH) can be said to have succeeded. Thisis apparent from the presence of targets that have been set byperformance UPTPK Sragen district that already can be achieved to themaximum, that is, the number of home is not livable as much 61,729units have done the repair as much of the 60,716 units or reach 98.36%.UPTPK responsiveness Sragen district in home improvement is notLivable (RTLH) can already be said either. Quality of service UPTPKSragen district in home improvement is not Livable (RTLH) can alreadybe said either. Accountability UPTPK Sragen district in homeimprovement is not Livable (RTLH) can be said to be quite good. Incarrying out its work, the obstacles experienced by UPTPK divided intothree things, namely, infrastructure, budget, and human resources (HR).In terms of facilities and infrastructure are still limited. In terms ofbudget, a budget that is related to the limited number of budgets for eachhelp only Rp 7.5 million. In the human resources associated with theleast amount of officers who still exist in terms of implementing theservice, handling, and poverty reduction in the Sragen district, making itby far the UPT-PK only serve the poor who proposed only.Keywords: Productivity, Service Quality, Responsiveness, Accountability andCorporate Responsibility